Conformational dynamics of CYP3A4 demonstrate the important role of Arg212 coupled with the opening of ingress, egress and solvent channels to dehydrogenation of 4-hydroxy-tamoxifen - Shahrokh, Kiumars; Cheatham, Thomas E.; Yost, Garold S. (Biochimica et biophysica acta, 2012)
Structure-based methods for P450 substrates are commonly used during drug development to identify sites of metabolism. However, docking studies using available X-ray structures for the major drug-metabolizing P450, CYP3A4, do not always identify binding modes supportive of the production of high-energy toxic metabolites. Minor pathways such as P450-catalyzed dehydrogenation have been experimentally shown to produce reactive products capable of forming biomolecular adducts which can lead to increased risk toxicities. 4-Hydroxy-tamoxifen (4OHT) is metabolized by CYP3A4 via competing hydroxylation and dehydrogenation reactions. Ab initio gas-phase electronic structural characterization of 4OHT was used to develop a docking scoring scheme. Conformational sampling of CYP3A4 with molecular dynamics simulations along multiple trajectories were used to generate representative structures for docking studies using recently published heme parameters. A key predicted binding mode was tested experimentally using site-directed mutagenesis of CYP3A4 and liquid chromatography–mass spectroscopy analysis. Docking with MD-refined CYP3A4 structures incorporating hexa-coordinate heme parameters identifies a unique binding mode involving ARG212 and channel 4, unobserved in the starting PDB ID: 1TQN X-ray structure. The models supporting dehydrogenation are consistent with results from in vitro incubations. Our models indicate that coupled structural contributions of the ingress, egress and solvent channels to the CYP3A4 active site geometries play key roles in the observed 4OHT binding modes. Thus adequate sampling of the conformational space of these drug-metabolizing promiscuous enzymes is important for substrates that may bind in malleable regions of the enzyme active-site. ► MD-refined P450 structures identify the importance of channels in CYP3A4 docking. ► A unique configuration is identified involving Arg212 in the dehydrogenation of 4OHT. ► CYP3A4 and CYP3A4-R212A show a decreased rate of dehydrogenation versus oxygenation.